2001
DOI: 10.1088/0031-9155/46/12/305
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The ability to control the shape of thermal coagulation was investigated for various interstitial heating applicators incorporating planar transducers and device rotation. Magnetic-resonance-compatible interstitial ultrasound applicators were constructed and the effects of ultrasound power, frequency, scan rate and heating time on lesion radius were studied in heating experiments in excised liver tissue. Continuous thermal lesions were generated by scanning heating applicators over a 180 angular sector. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Directional heating can be realized through the use of sectored cylindrical, 21 curvilinear, 22 or planar transducers. 23,24 Multielement transducer configurations can be utilized to adjust the energy distribution along the length of the heating applicator. 25,26 Multifrequency transducers can be used to adjust the radial distance of energy deposition from each transducer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Directional heating can be realized through the use of sectored cylindrical, 21 curvilinear, 22 or planar transducers. 23,24 Multielement transducer configurations can be utilized to adjust the energy distribution along the length of the heating applicator. 25,26 Multifrequency transducers can be used to adjust the radial distance of energy deposition from each transducer.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Multifrequency transducers can be used to adjust the radial distance of energy deposition from each transducer. 27 These transducer designs enable the generation of intricate thermal damage patterns in three dimensions, 22,23,28,29 which can be important in reducing some of the side effects common in other forms of therapy for prostate cancer. 4 Equally important is the capability to monitor the heating pattern produced during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Control over the spatial deposition of energy can be achieved with some ultrasoundbased transurethral heating applicators. Directional heating can be realized through the use of sectored cylindrical transducers (Diederich et al 2000) or planar transducers (Chopra et al 2001, Lafon et al 1998. Multi-element transducer configurations can be utilized to adjust the energy distribution along the length of the heating applicator (Diederich and Burdette 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Multi-frequency transducers can enable greater control over the radial energy deposition from each transducer (Chopra et al 2003). These transducer designs enable the generation of intricate thermal damage patterns in three dimensions (Chopra et al 2001, Tyreus et al 2003 which is particularly important in avoiding the side effects common in other forms of therapy for prostate cancer (Potosky et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Deardorff et al (1998) produced large lesions approximately 30 mm in diameter (measured perpendicular to transducer axis), using a single-element cylindrical ultrasound transducer (2.5 mm od and 10 mm length, 7.2 MHz resonant frequency). Chopra et al (2001) showed that a single-element scanned planar transducer (3 mm × 15 mm) produced thermal lesions in excised bovine liver tissue with a maximum diameter of 36 mm at 4.7 MHz, also measured perpendicular to the axis of the transducer. These ultrasound-generated lesions are considered large in comparison to those produced by other single, interstitial thermal therapy applicators such as lasers and microwave antennae, but are smaller than the lesions produced by our helical coils.…”
Section: Discussionmentioning
confidence: 99%